Towards digital manufacturing : robotic path planning on free-form surfaces from 3D-scanned data - Chew, Leonard Wei Jie (2019)
This report is a detailed documentation of a year’s work on the robotic path planning of a HEBI robotic arm with 4 degrees of freedom (DOF). The author’s role in this project is to implement a natural approach to path-planning for the robotic arm based on the geometry of triangulated surfaces derived from 3D scans. A 3D modelling program called Blender was used to project 3D scans of surfaces as models formed by meshes in the program, and path planning would direct the robotic arm from one point to another on the projected surface. This report contains a literature survey of methods and approaches that could be done and implemented in the project. The first half of the project consists of conducting research on various materials related to the project and to practice using Blender for the second half of the project. Future work that has to be done for the project would be discussed as well.